The role of the cooperative model in sustainable development: Case of agricultural cooperatives in the SOUSS MASSA region in Morocco - Jamal, Oulaich (Eximia, 2023)
The question of sustainable development is generally based on the activity of economic actors in implementing the challenges of the sustainable development model. In developing countries in Morocco, and which continues to exist with my new industrialized countries, cooperatives are one of the engines of growth and development, allowing initially reducing the scale of precariousness, inequalities and underdevelopment between regions and cities. At this level, cooperatives have several commitments; in particular, respect for the environment through compliance with standards that serve to assess the latter is capacity to satisfy the needs of its customers, the repair of wealth and the rise in inequalities. . In this work, we seek to ensure that sustainable development is strongly linked to the development of the cooperative model.